Ionospheric Oxygen ions in the dayside magnetosphere. (15th November 2020) - Fuselier, Stephen A.
Abstract: Prior to its discovery, O + from the Earth's high-latitude ionosphere was not expected to be present in any significant amount in the magnetosphere. It is now known that O + can dominate ionospheric outflow and dominate magnetotail composition during geomagnetically active times. Observations from the Magnetospheric Multiscale (MMS) mission are used here to illustrate properties of O + in the dayside outer magnetosphere and to identify gaps in the knowledge of this ionospheric ion. When the interplanetary magnetic field (IMF) is southward, O + from the high-latitude ionosphere convects to the magnetotail then from the magnetotail to the dayside. The two primary O + populations observed in the dayside magnetosphere are the ring current and warm plasma cloak. They are sometimes distinguishable by their energy, although velocity-space distribution functions are often needed to make a true distinction. There are several sinks for these populations in the dayside magnetosphere. One important sink is the dayside magnetopause. While much is understood about O + in the dayside magnetosphere, there are several open questions detailed in the final section of the paper. Highlights: The discovery of ionospheric O + in the magnetosphere in 1972 was a surprise. O + originates from the Earth's high-latitude ionosphere and convects into the Earth's magnetotail for southward IMF. There are two O + populations in the dayside magnetosphere: The ring current and the warm plasma cloak. There are several loss mechanisms for O +, and loss through the dayside magnetopause is one important mechanism. Open questions remain on the sources, transport, and loss mechanisms of O + and on the effects of O + in the magnetosphere.